La agricultura orgánica en las exportaciones de México, Argentina, Uruguay (2010-2017) (2018)
Organic agriculture is an alternative that was found to mitigate some effects generated by conventional agriculture on the environment. The conventional way of cultivating has increased the environmental problems since this generates a change in the cultivated lands, in the waters that surround them and in the air; this as a result of the use of pesticides, herbicides, chemicals among many more elements than their components and their form of application, form different toxic compositions for human health and for the environment.